The reliability of the Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI) among dermatologists, rheumatologists and neurologists. (22nd December 2016) - Tiao, J.; Feng, R.; Bird, S.; Choi, J.K.; Dunham, J.; George, M.; Gonzalez‐Rivera, T.C.; Kaufman, J.L.; Khan, N.; Luo, J.J.; Micheletti, R.; Payne, A.S.; et al.
Summary: Background: Previous studies have shown that skin disease in dermatomyositis (DM) is best assessed using the Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI). Although the CDASI has been validated for use by dermatologists, it has not been validated for use by other physicians such as rheumatologists and neurologists, who also manage patients with DM and assess skin activity in clinical trials. Objectives: To assess the reliability of the CDASI among dermatologists, rheumatologists and neurologists. Methods: Fifteen patients with cutaneous DM were assessed using the CDASI and the Physician Global Assessment (PGA) by five dermatologists, five rheumatologists and five neurologists. Results: The mean CDASI activity scores for dermatologists, rheumatologists and neurologists were 21·0, 21·8 and 20·8, respectively. These mean scores were not different among the specialists. The CDASI damage score means for dermatologists, rheumatologists and neurologists were 5·3, 7·0 and 4·8, respectively. The mean scores between dermatologists and rheumatologists were significantly different, but the means between dermatologists and neurologists were not. The intraclass correlation coefficients (ICCs) for interrater reliability for CDASI activity and damage were good to excellent for dermatologists and rheumatologists, and moderate to excellent for neurologists. The ICCs for intrarater reliability for CDASI activity and damage were excellent for dermatologists and rheumatologists and moderate to excellent for neurologists. The PGA displayed lower interrater and intrarater reliability relative to the CDASI. Conclusions: Our results confirm the reliability of the CDASI when used by dermatologists and rheumatologists. The data for its use by neurologists were not as robust. Abstract : What's already known about this topic? The Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI) is a reliable and valid outcome measure to assess cutaneous disease in adult dermatomyositis (DM) when used by dermatologists What does this study add? The study expands the application of the CDASI in adult patients with DM for use by rheumatologists. The study suggests that neurologists are also capable of using the CDASI to assess skin in adult patients with DM, with neurologists achieving moderate interrater reliability. Linked Comment: Kurtzman and Vleugels. Br J Dermatol 2017; 176 :296–297 .